The association between blood glucose levels and lipids or lipid ratios in type 2 diabetes patients: A cross-sectional study - Wang, Liqun; Yan, Ning; Zhang, Min; Pan, Ruiping; Dang, Yuqi; Niu, Yang (Frontiers in Endocrinology, 2022)
Background Lipids and lipid ratios are associated with complications of diabetes mellitus type 2 (T2DM), such as cardiovascular disease, but the relationship between blood glucose levels and lipid or lipid ratios is not fully understood in T2DM patients. This study assesses the association between blood glucose levels and lipid or lipid ratios in a cohort of T2DM patients. Methods A total of 1,747 Chinese T2DM patients from the Ningxia province of China were included in this cross-sectional study. Lipid parameters, including triglycerides (TG), total cholesterol, high-density lipoprotein, low-density lipoprotein, and fasting blood glucose levels were measured quantitatively using standard methods. Fasting blood glucose was divided into three levels. A multiple mixed-effect linear regression model was conducted to identify a potential association between blood glucose and lipid parameters. Results There was a positive association between blood glucose and TG levels (β=0.34, 95% CI: (0.20, 0.48), p <0.01); every 1 mmol/L increase in blood glucose levels resulted in a 0.34 mmol/L increase in TG. Blood glucose levels were also associated with high LDL (β=0.08, 95% CI: (0.02, 0.14), p <0.01), TG/HDL-C (β=0.31, 95% CI: (0.13, 0.49), p <0.01), and LDL-C/HDL-C (β=0.13, 95% CI: (0.06, 0.20), p<0.01) levels. After controlling for demographic variables, health-related behaviors, and physical health variables, a positive association between blood glucose levels and TG (β=0.31, 95% CI: (0.17, 0.45), p <0.01) and LDL-C (β=0.08, 95% CI: (0.02, 0.13), p <0.01) levels and an in increase in TG/HDL-C (β=0.28, 95% CI: (0.09, 0.46), p <0.01) and LDL-C/HDL-C (β=0.11, 95% CI: (0.04, 0.18), p <0.01) ratios was found. Conclusion A correlation between blood glucose levels and serum lipids or lipid ratios has been established in this study. Good control of blood glucose levels and lipid profiles or ratios is essential for patients with T2DM. To better inform the management of T2DM, there should be additional research on blood glucose levels and lipids or lipid ratios.